2022
DOI: 10.3390/antiox11051028
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Effects of Exercise on the Systemic Effects of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a progressive degenerative disorder and a leading cause of dementia in the elderly. The etiology of AD is multifactorial, including an increased oxidative state, deposition of amyloid plaques, and neurofibrillary tangles of the tau protein. The formation of amyloid plaques is considered one of the first signs of the illness, but only in the central nervous system (CNS). Interestingly, results indicate that AD is not just localized in the brain but is also found in organs distant fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 145 publications
1
11
0
Order By: Relevance
“…LONP1 is responsible of removal of damaged proteins in the mitochondria, and because of excessive generation of ROS in this organelle this has a vital role in cell survival. AD is known to associated with increased oxidative stress (40,41), therefore the present novel observation, that exercise and postbiotic increase LONP-1 level and activity adds an important new mosaic to the better understanding of exercise and postbiotic treatments on AD.…”
Section: Discussionmentioning
confidence: 84%
“…LONP1 is responsible of removal of damaged proteins in the mitochondria, and because of excessive generation of ROS in this organelle this has a vital role in cell survival. AD is known to associated with increased oxidative stress (40,41), therefore the present novel observation, that exercise and postbiotic increase LONP-1 level and activity adds an important new mosaic to the better understanding of exercise and postbiotic treatments on AD.…”
Section: Discussionmentioning
confidence: 84%
“…The only longitudinal study where the authors considered this relationship showed no relation between favorable changes in cardiorespiratory fitness evoked by intense aerobic exercise and myelin expansion (Mendez Colmenares et al, 2021). This finding is somewhat contradictory to the belief that exercise-induced changes in cardiovascular performance represent a key element in cognitive improvement (Aczel et al, 2022;Maleki et al, 2022;Renke et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, removing the excessive accumulation of Aβ is an important train of thought in the treatment of AD. Exercise is considered an effective way to prevent and treat AD; such effectiveness may be related to the capability of exercise to participate in the clearance of the excessive accumulation of Aβ in the brain ( Radak et al, 2010 ; Aczel et al, 2022 ). Adlard et al (2005) published the study titled, “voluntary exercise decreases amyloid load in a transgenic model of Alzheimer’s disease,” in the Journal of Neuroscience, and it was possibly the earliest study on the clearance of Aβ by exercise.…”
Section: Discussionmentioning
confidence: 99%